Prospective validation of the Eastern Staging in predicting survival after surgical resection for patients with hepatocellular carcinoma: a multicenter study from China. Issue 1 (January 2023) - Yang, Shun-Chao; Liang, Lei; Wang, Ming-Da; Wang, Xian-Ming; Gu, Li-Hui; Lin, Kong-Ying; Zhou, Ya-Hao; Chen, Ting-Hao; Gu, Wei-Min; Li, Jie; Wang, Hong; Chen, Zhong; et al.
Abstract: Background: The Eastern Staging System, which was specially developed for patients undergoing surgical resection for hepatocellular carcinoma (HCC), has been proposed for more than ten years. To prospectively validate the predictive accuracy of the Eastern staging on long-term survival after HCC resection. Methods: Patients who underwent hepatectomy for HCC from 2011 to 2020 at 10 Chinese hospitals were identified from a prospectively collected database. The survival predictive accuracy was evaluated and compared between the Eastern Staging with six other staging systems, including the JIS, BCLC, Okuda, CLIP, 8th AJCC TNM, and HKLC staging. Results: Among 2365 patients, the 1-, 3-, and 5-year overall survival rates were 84.2%, 64.5%, and 52.6%, respectively. Among these seven staging systems, the Eastern staging was associated with the best monotonicity of gradients (linear trend χ 2 : 408.5) and homogeneity (likelihood ratio χ 2 : 447.3), and the highest discriminatory ability (the areas under curves for 1-, 3-, and 5-year mortality: 0.776, 0.787, and 0.768, respectively). In addition, the Eastern staging was the most informative staging system in predicting survival (Akaike information criterion: 2982.33). Conclusion: Using a large multicenter prospectively collected database, the Eastern Staging was found to show the best predictive accuracy on long-term overall survival in patients with resectable HCC than the other 6 commonly-used staging systems. Graphical abstract: Image 1